Integrating Concentrated Optics for Ambient Perovskite Solar Cells - Maria Khalid; Anurag Roy; Shubhranshu Bhandari; Senthilarasu Sundaram; Tapas K. Mallick (Energies, 2021)
Metal halide perovskite solar cells (PSCs) are considered an effectual way to enhance photovoltaic (PV) properties, leading to low-cost and high efficiency. PSCs have experienced rapid improvement in the last ten years. The device’s energy production increases extensively in the presence of concentrated light. The use of concentrated optics in solar cells has spurred the PV industry towards tremendous research. Incorporating the concentrated optic into the PV system as a concentrated PV (CPV) means it can capture light effectively and operate at increased efficiencies under concentrated irradiance. This work addresses an initial assessment of the power conversion efficiency (PCE) enhancement of the ambient PSCs by externally integrating concentrated optics. Significantly, the concentrated optics exhibit ~90% of the PCE enhancement under the solar irradiance of 400 W/m2, whereas 16% of the PCE increase was observed when the solar irradiance changed to 1000 W/m2. During optics integration, a considerable elevation of short-circuit current predominately facilitated the overall efficiency enhancement of the PSC. A systematic PV parameters effect on the optic integration on PSCs was further scrutinized. Therefore, this work signifies a possible way to alleviate the PCE of carbon-based PSC using concentrated optics. This work focuses on integrating CPVs into PSCs, preventing PSC stability and scalability issues, with light conditioning techniques.